Fracture, Fatigue, Failure and Damage Evolution, Volume 8 Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Zehnder, Alan T.; Carroll, Jay; Hazeli, Kavan; Berke, Ryan B.; Pataky, Garrett; Cavalli, Matthew; Beese, Alison M.; Xia, Shuman (Conference Proceedings of the Society for Experimental Mechanics Series, 2017)
Fracture, Fatigue, Failure and Damage Evolution, Volume 8 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the eighth volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: In-situ Techniques for Fracture & Fatigue General Topics in Fracture & Fatigue Fracture & Fatigue of Composites Damage, Fracture, Fatigue & Durability Interfacial Effects in Fracture & Fatigue Damage Detection in Fracture & Fatigue.